2014
DOI: 10.1007/s11136-014-0623-x
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in children and adolescents with celiac disease: patient-driven data from focus group interviews

Abstract: Children and adolescents showed large diversity in how much impact CD has on their HRQOL. Different ways of coping with CD and GFD were identified. Findings will be used to generate a patient-driven disease-specific questionnaire to measure HRQOL in children and adolescents with CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 36 publications
5
35
0
1
Order By: Relevance
“…These dilemmas are related to difficulties in social relationships and management of daily life in order to adhere to the GFD [23]. Also children with CD experience similar difficulties, as described in recent studies [13,24]. We also found that presence of co-morbidities negatively affected QOL, in particular the Psycho-Social Health and Total Scores.…”
Section: Discussionsupporting
confidence: 75%
“…These dilemmas are related to difficulties in social relationships and management of daily life in order to adhere to the GFD [23]. Also children with CD experience similar difficulties, as described in recent studies [13,24]. We also found that presence of co-morbidities negatively affected QOL, in particular the Psycho-Social Health and Total Scores.…”
Section: Discussionsupporting
confidence: 75%
“…Recent focus group interviews with 8–18 year olds ( n = 23) from Denmark revealed stressors similar to those identified by Olsson et al . and Biagetti et al .…”
Section: Burden Of a Gluten‐free Diet: Studies In Adolescentssupporting
confidence: 65%
“…Recent focus group interviews with 8-18 year olds (n = 23) from Denmark (28) revealed stressors similar to those identified by Olsson et al (24) and Biagetti et al (26) . Participants experienced negative reactions from peers if it was felt they were given preferential treatment as a result of having CD.…”
Section: Burden Of a Gluten-free Diet: Studies In Adultssupporting
confidence: 64%
“…Topics that have emerged from qualitative analyses include body image and self-esteem (Chang et al, 2016), as well as emotional impact, thoughts about future, and coping with social situations (Skjerning, Mahon, Husby, & DunnGalvin, 2014). If we assume that the focus groups were able to collect the full range of experiences of short stature in each country, then differences in the number of statement categories could be a sign of differences in experience between countries.…”
Section: Discussionmentioning
confidence: 99%
“…Socioemotional issues play an important role in children with chronic conditions, as suggested by studies that used focus groups to assess HrQoL in children with chronic conditions like celiac disease or neonatal brachial plexus palsy (Chang et al, ). Topics that have emerged from qualitative analyses include body image and self‐esteem (Chang et al, ), as well as emotional impact, thoughts about future, and coping with social situations (Skjerning, Mahon, Husby, & DunnGalvin, ). If we assume that the focus groups were able to collect the full range of experiences of short stature in each country, then differences in the number of statement categories could be a sign of differences in experience between countries.…”
Section: Methodsmentioning
confidence: 99%